Application of the Hybrid Contract Concept to Rahn Products At the Sharia Pawnshop - fattah, Abd Fattah; Herdiana Abdurrahman, Nana; Yoyok, Yoyok (Yayasan Mentari Madani, 2024)
Changes and the growth of shari'ah financial problems have faced widespread challenges. Among the important pillars for creating shari'ah financial products in serving the demands of modern society is the development of hybrid conctract (multi-contract). This paper analyzes rahn products that are widely practiced in shari'ah financial institutions, especially shari'ah pawnshops, from the point of hybrid contract. This research uses a qualitative approach with a type of case study research at Pegadaian Syariah Jombang. One of the data collection techniques is in the form of documentation, namely a rahn transaction agreement document between pawn customers and the Jombang Regency shari'ah pawnshop. Data analysis of this study in addition to using the fiqh approach also uses a substantive-normative approach in Islamic legal thinking. The results showed that rahn products in shari'ah pawnshops are still questionable shari'ah practices. If examined more deeply based on the criteria of permissible hybrid contracts, then this product can be included in the prohibited hybrid contract, because it is included in the combination of buying and selling with debts prohibited by hadith and scholars, because it combines two contracts that contradict its character and nature.